An Exploratory Study on Perceptions and Use of Technology by Novice and Future Teachers: More Information and Less On-Line Collaboration? - Petrucco, Corrado; Grion, Valentina (International journal of digital literacy and digital competence, 2015)
The article discusses the factors that affect the choice of teachers to integrate technology in their teaching and presents the results of a questionnaire administered to 805 teachers attending professional development training courses (TFA and PAS) in the Veneto Region (Northern Italy). The research is aimed at collecting data for the development of a teachers training program that is effective in motivating them to a broader and more effective use of technology. The study reveals how teachers still have little consideration for the potential of interactive and collaborative technology, preferring to use technology for searching information and materials rather than for discussion and participation in on-line communities with their peers, in order to improve their teaching and towards a collaborative construction and sharing of knowledge. The study also confirms the findings in the literature on the subject relative to a number of factors (internal and external) that are perceived as obstacles to the decision to integrate technology in education and proposes specific training activities that are useful in order to remove them.